The behavioral model and game theory - Askari, Gholamreza; Gordji, Madjid Eshaghi; Park, Choonkil (Humanities & social sciences communications, 2019)
The rational choice theory is based on this idea that people rationally pursue goals for increasing their personal interests. Here, we present a new concept of rational choice as a hyper-rational choice in which the actor thinks about profit or loss of other actors in addition to his personal profit or loss and then will choose an action that is desirable to him. We implement the hyper-rational choice to generalize and expand the game theory. Results of this study will help to model the behavior of people considering environmental conditions, the type of behavioral interaction, valuation system of itself and others, and system of beliefs and internal values of societies. Hyper-rationality helps us understand how human decision-makers behave in interactive decisions.